Diese Präsentation wurde erfolgreich gemeldet.

Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
Anzeige
×

1 von 1 Anzeige

# help me solve this equation 2-2x-3-x plus 3-1 pleaseSolution.docx

help me solve this equation 2/2x-3/x plus 3=1 please
Solution
Subtracting three on both sides we will get 2/2x-3/x = -2................1) Find the common denominator term and subtract the given function. we will get the common denominator as 2x^2 now, turn the given fraction into its equivalent term 2/2x = multiplying x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 2/2x = 2x/2x^2 and for 3/x = multiplying 2x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 3/x = (3 * 2x)/2x^2 = 6x/2x^2 now, replace the fraction of equation 1 with its equivalent one we will get.. 2x/2x^2 - 6x/2x^2 = -2 (2x - 6x)/2x^2 = -2 -4x/2x^2 = -2 -2/x = -2 x = 1
.

help me solve this equation 2/2x-3/x plus 3=1 please
Solution
Subtracting three on both sides we will get 2/2x-3/x = -2................1) Find the common denominator term and subtract the given function. we will get the common denominator as 2x^2 now, turn the given fraction into its equivalent term 2/2x = multiplying x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 2/2x = 2x/2x^2 and for 3/x = multiplying 2x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 3/x = (3 * 2x)/2x^2 = 6x/2x^2 now, replace the fraction of equation 1 with its equivalent one we will get.. 2x/2x^2 - 6x/2x^2 = -2 (2x - 6x)/2x^2 = -2 -4x/2x^2 = -2 -2/x = -2 x = 1
.

Anzeige
Anzeige

## Weitere Verwandte Inhalte

Anzeige

### help me solve this equation 2-2x-3-x plus 3-1 pleaseSolution.docx

1. 1. help me solve this equation 2/2x-3/x plus 3=1 please Solution Subtracting three on both sides we will get 2/2x-3/x = -2................1) Find the common denominator term and subtract the given function. we will get the common denominator as 2x^2 now, turn the given fraction into its equivalent term 2/2x = multiplying x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 2/2x = 2x/2x^2 and for 3/x = multiplying 2x in the denominator term will result the common denominator term 2x^2 and we also need to multiply the same term with numerator too, we will get 3/x = (3 * 2x)/2x^2 = 6x/2x^2 now, replace the fraction of equation 1 with its equivalent one we will get.. 2x/2x^2 - 6x/2x^2 = -2 (2x - 6x)/2x^2 = -2 - 4x/2x^2 = -2 -2/x = -2 x = 1